Information for Agricultural and Rural Development in ACP Countries: summary report - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The areas highlighted were the development of support programmes to improve stakeholders' ability to implement information strategies, the promotion of increased networking, and the improvement of information generation and supply using appropriate media.